MANAJEMEN KEUANGAN SEKOLAH DI SMK YABUJAH SEGERAN JUNTINYUAT INDRAMAYU PADA 2019 - Yuyud Susilo (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2022)
Financial Management in Vocational High schools must be considered properly because it concerns the independence of a school. Therefore, this study aims to analyze school financial management in fulfilling educational infrastructure at SMK Yabujah Segeran Juntinyuat, Indramayu. This research uses a qualitative approach to the type of case study. The data collection technique was carried out using interviews, observations, and documentation. The data analysis technique uses data reduction, data display, and conclusion drawing/verification. Checking the validity of the data is carried out through; credibility, transferability, dependability, and confirmability. The results showed that school financial management in fulfilling educational infrastructure at SMK Yabujah Segeran Juntinyuat Indramayu was carried out through school budgeting, school financial accounting, school financial accounting, school financial accountability.